Racism and Homosexual in "Go Tell It on The Mountain" Novel By James Baldwin - Usman, Rahmi; Irmayani; Said, Ratna (JLE: Journal of Literate of English Education Study Program, 2024)
This study explores the development of Baldwin's racial and homosexual identity in his novel Go Tell it on the Mountain. It examines how Baldwin's experiences as both a homosexual and an African American shaped his identity and his efforts to engage with society. Baldwin’s awareness of racism and homophobia in America positioned him as a public figure advocating for both black and LGBTQ+ communities, deeply influencing his writing. The study uses Henri Tajfel and John Turner's Social Identity Theory (SIT) to understand how Baldwin's identity was formed. The first stage explores Baldwin’s self-awareness as part of social groups like the black and homosexual communities. The second stage analyzes his shift from recognizing his identity to actively defining it. The third stage looks at the psychological and social impact of his group identity, highlighting how racism and homophobia shaped his work and the messages he conveyed. The study concludes that Baldwin’s identity was shaped by his environment and the double oppression he faced—both as a homosexual and as a black man. SIT provides a valuable framework for understanding how group affiliation influences individual identity and broader social dynamics.